(untitled) (Journal of Educational Sciences, 2023)
The article was written within the framework of the Project of the Ministry of Science and Higher Education of the Republic of Kazakhstan IRN AR 14872130 “Formation of professional self-determination of students with special educational needs (SEN) as a national strategy in the field of inclusive education in the Republic of Kazakhstan” (2022-2024).The article raises the issues of creating an inclusive environment in the higher education system of the Republic of Kazakhstan, which contributes to the professional self-determination of students with special educational needs and their further successful employment. Based on the materials of the express survey, the experience of universities in creating conditions for students, allowing them to self-determine themselves in the conditions of higher education and acquire the necessary social and labor skills, was analyzed. In particular, the results of an express survey of students with special educational needs demonstrated the features and reasons for choosing a profession and further employment options, depending on personal and physiological characteristics, helped to clarify the gaps in creating an inclusive university environment, to determine the prospects for further purposeful activities to form the readiness of this category of students for successful professional self-determination. Key words: inclusion, inclusive education, persons with disabilities, students with special educational needs (SEN), professional self-determination.